RESEARCH INTO THE NURSING STUDENTS' KNOWLEDGE OF NOSOCOMIAL INFECTIONS IN PEDIATRIC WARDS - Donka Sultanova (Science & Research)

(untitled)
Nosocomial infections are a problem affecting healthcare worldwide, and pediatric wards are one of the highest risk areas for the development of such infections. In the process of providing health care to children in hospital wards, students are required to observe the specified statutory precautions that are necessary to prevent the occurrence and transmission of nosocomial infections. Insufficient awareness, lack of knowledge and non-compliance with these measures pose a huge risk to the lives and health of pediatric patients. The aim of the present study was to investigate the knowledge of nursing students regarding the prevention and transmission of nosocomial infections in pediatric wards. Materials and Methods: Literature analysis was applied. A cross-sectional empirical study. The opinion of 60 nursing students, who had clinical practice in the Department of Pediatrics at the Dr. Ivan Seliminski Hospital, Sliven, was studied. The research was conducted between December 2021 and April 2022. Results: Most of the subjects were aware of the problems associated with nosocomial infections and the precautions related to them. Conclusions: The up-to-date information and theoretical training they receive need to correspond to the activities they practice in pediatric wards in order to provide quality health care.